Online determinants of e-customer satisfaction: application to website purchases in tourism - Pereira, H.; Salgueiro, M. F.; Rita, P. (Service Business, 2017)
This paper examines the influence of four variables on online tourism customer satisfaction: website image perceptions, online routine, online knowledge, and customer innovativeness, and their simultaneous effects. The analysis gauges the moderating role of three socio-demographic characteristics: gender, age group, and educational background. A sample of 3188 regular online consumers of the Portuguese leader in the tourism sector was analyzed using structural equation modeling. Results show that website image, routine, and knowledge significantly influence e-customer satisfaction. Only gender moderates the impact of website knowledge on e-satisfaction. These results entail a better understanding of customer specificities, with practical actions for addressing their real needs and expectations.